Uranium diffusion and time-dependent adsorption–desorption in soil: a model and experimental testing of the model - Darmovzalova, Jana; Boghi, Andrea; Otten, Wilfred; Eades, Lorna J.; Roose, Tiina; Kirk, Guy J. D. (Wiley, 2019)
Most past research on uranium (U) transport and reaction in the environment has been concerned with groundwater contamination and not with uptake by plants or soil biota, both of which operate over much smaller time and distance scales. We developed and tested a model of U diffusion and reaction in soil at scales appropriate for uptake by plant roots, based on a model we developed in an earlier paper. The model allows for the speciation of U with hydroxyl, carbonate and organic ligands in the soil solution, and the nature and kinetics of sorption reactions with the soil solid. The model predictions were compared with experimentally‐measured concentration‐distance profiles of U in soil adjusted to different pHs and CO2 pressures. Excellent agreement between observed and predicted profiles was obtained using model input parameters measured or otherwise estimated independently of the concentration‐distance profiles, showing that the model was a correct description of the system and all important processes were allowed for. The importance of the kinetics of U adsorption and desorption on the time‐scale of diffusion through the soil is highlighted. The results are discussed in terms of the uptake of U by plant root systems, as modelled in the earlier paper.